Sustainability Burden or Boost? Examining the Effect of Public Debt on Renewable Energy Consumption in Sub-Saharan Africa - Favour Chidinma Onuoha; Stephen Kelechi Dimnwobi; Kingsley Ikechukwu Okere; Chukwunonso Ekesiobi (African Governance and Development Institute (AGDI), 2023)
Given that the development of renewable energy is regarded as a sustainable alternative to the realization of environmental quality, it is not surprising that the discussion of the sustainability of the world's energy sources continues to expand. While renewable energy has a negligible impact on environmental degradation, developing regions like sub-Saharan Africa (SSA) is restricted by the capital-intensive investment requirements of the burgeoning renewable energy market. To explore the significance of available funding sources on renewable energy development in the region, this study investigates the influence of public debt on renewable energy consumption (REC) in a panel of 29 SSA countries, in full and sub-regional categorizations. A combination of the instrumental variable generalized method of moment (IV-GMM) approach and the two-stage least squares estimator was applied to achieve the goal of the study. Overall, our findings indicate that public debt, carbon emission, financial development, and economic growth exert a negative and significant linkage with renewable energy, while urbanization has a positive and significant influence. Aware of the study findings, appropriate policy prescriptions are proposed to improve the debt-financed funding for the development of the renewable energy sector in SSA.
Keywords: 330; Public Debt; Renewable Energy; Financial Development; Economic Growth; Carbon Emission